2006
DOI: 10.1111/j.1463-1318.2006.01048.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes in 2748 patients referred to a colorectal two‐week rule clinic

Abstract: A specialist nurse-led, one-stop TWR clinic for suspected colorectal cancer is sustainable and can be run successfully with over 90% of referrals seen within the targeted time period. The proportion of non-conforming referrals was high and a large number of advanced and unstaged tumours was observed. Low numbers of proximal tumours were detected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
24
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 8 publications
5
24
1
Order By: Relevance
“…The majority (82%) of referrals met the criteria for assessment in the rapid-access clinic, indicating that primary care physicians are making appropriate use of resources by means of an established referral pathway and the use of a referral pro forma. In contrast, Smith et al 9 and Debnath et al 10 found that there was a very high proportion of nonconforming referrals (50%-62%). The reason for the high conformity of referrals in our unit may be due to a well-established and open relationship with GP practices, with the rapid access clinic now running for more than 15 years.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…The majority (82%) of referrals met the criteria for assessment in the rapid-access clinic, indicating that primary care physicians are making appropriate use of resources by means of an established referral pathway and the use of a referral pro forma. In contrast, Smith et al 9 and Debnath et al 10 found that there was a very high proportion of nonconforming referrals (50%-62%). The reason for the high conformity of referrals in our unit may be due to a well-established and open relationship with GP practices, with the rapid access clinic now running for more than 15 years.…”
Section: Discussionmentioning
confidence: 89%
“…Whether the use of 2-week rule clinics has a positive effect on early diagnosis of CRC and subsequent survival rates and outcomes has been challenged. 9,16 This assumption was based on evidence that screening for CRC reduces mortality, therefore implying that early diagnosis confers an advantage on survival. 17 As early as 20 years ago, studies suggested a beneficial effect of a single flexible sigmoidoscopy as a screening tool for CRC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cancer detection rate in our study was only 3%, which is much lower than other reported series, with rates of 6-14% in a 2WW population. [20][21][22][23][24][25][26] Our detection rate may have been influenced by the exclusion of male patients. However, there is a suggestion that detection rates are falling 27 with referrals increasing, particularly following the Be Clear on Cancer campaign in 2012.…”
Section: Discussionmentioning
confidence: 99%
“…Large numbers of patients are seen through this pathway but the literature shows that only 6-14% of patients referred via this route are diagnosed with cancer and this is decreasing over time. [20][21][22][23][24][25] Experience suggests that the secondary care system does not have the capacity for full investigation and management of the remaining patients with functional and benign colorectal disorders that may be identified. This could represent a potentially significant need for development of pelvic floor services.…”
mentioning
confidence: 99%